The Handbook of infrared and raman characteristic frequencies of organic molecules - Lin-Vien, Daimay; Colthup, Norman B.; Fateley, William G.; Grasselli, Jeanette G. (Professor) (Academic Press, 1991)
This necessary desk reference for every practicing spectroscopist represents the first definitive book written specifically to integrate knowledge about group frequencies in infrared as well as Raman spectra. In the spirit of previous classics developed by Bellamy and others, this volume has expanded its scope and updated its coverage. In addition to detailing characteristic group frequencies of compounds from a comprehensive assortment of categories, the book includes a collection of spectra and a literature search conducted to verify existing correlations and to determine ways to enhance correlations between vibrational frequencies and molecular structure. Particular attention has been given to the correlation between Raman characteristic frequencies and molecular structure. Key Features * Constitutes a necessary reference for every practicing vibrational spectroscopist * Provides the new definitive text on characteristic frequencies of organic molecules * Incorporates group frequencies for both infrared and Raman spectra * Details the characteristic IR and Raman frequencies of compounds in more than twenty major categories * Includes an extensive collection of spectra * Compiled by internationally recognized experts.